234k views
4 votes
Rearange the equation to isolate a. (a+b/c)(d-e)=f find a =​

1 Answer

2 votes

Answer:


a=(f)/(d-e)-(b)/(c)

Step-by-step explanation:

Hello.

In this case, for the equation:


(a+b/c)(d-e)=f

For isolating a, we must first pass (d-e) to divide at the other side as it is initially multiplying:


a+b/c=(f)/((d-e))

Next, as b/c is adding, it passes to subtract at the other side in order to finally isolate a:


a=(f)/(d-e)-(b)/(c)

Best regards!

User Himanshu Joshi
by
4.9k points